2013
DOI: 10.1186/1475-2867-13-28
|View full text |Cite|
|
Sign up to set email alerts
|

Functional disruption of macrophage migration inhibitory factor (MIF) suppresses proliferation of human H460 lung cancer cells by caspase-dependent apoptosis

Abstract: BackgroundMacrophage migration inhibitory factor (MIF) is important in regulating cell proliferation and apoptosis in both normal and cancerous cells, and may be important in cancer progression and metastasis. In human non-small cell lung cancer (NSCLC), the underlying mechanisms responsible for MIF-dependent regulation of cellular proliferation, and cell death remain poorly appreciated.MethodsThe human H460 lung cancer cell-line was treated with an optimally determined dose of 50 pmol/ml MIF siRNA, following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…reported that knockdown of MIF resulted in a substantial decrease in migratory potential of lung adenocarcinoma cells. Another study showed that knockdown of MIF dampened cell proliferation by enhancing apoptosis in lung cancer cell . Goto et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that knockdown of MIF resulted in a substantial decrease in migratory potential of lung adenocarcinoma cells. Another study showed that knockdown of MIF dampened cell proliferation by enhancing apoptosis in lung cancer cell . Goto et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that knockdown of MIF dampened cell proliferation by enhancing apoptosis in lung cancer cell. 20 Goto et al 11 reported that MIF expression was inversely correlated with miR-451 expression, and MIF expression and phosphorylated Akt expression after transfection of miR-451-mimic was suppressed, as were cell proliferation and migration in NSCLC cell lines. Moreover, they found that SCC and highgrade tumor showed a lower expression of miR-451 than adenocarcinoma and low-grade tumor in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the present study confirmed MIF as a direct target gene of miR-451, and showed that miR-451 negatively regulated the expression of MIF expression by directly targeting the 3'UTR of MIF mRNA in the NB cells. MIF is considered to be a multifunctional cytokine, secreted by a variety of cells, including macrophages, lymphocytes, eosinophils, epithelial cells and endothelial cells (25). It is predominantly immunoregulatory, serving important roles in inflammation, and in cell-mediated and innate immunity (26)(27)(28).…”
Section: A B C D Ementioning
confidence: 99%
“…The proangiogenic factor, PDGFaa, was shown to act as a survival factor, to inhibit apoptosis, to increase vessel density [45], and to stimulate reorganization of actin [46]. The pro-inflammatory factor, MIF, was shown to promote metastases by (i) initiating the NF-ĸB signaling cascade resulting in the secretion of pro-inflammatory cytokines such as IL-8, TNF-α, IL-1, and IL-6 ,(ii) promoting MMPs activity, (iii) increasing tumor-infiltration of myeloid-derived suppressor cells [47][48], (iv) promoting EMT [49], and (v) exerting pro-survival [50] and anti-apoptotic activities [51]. Overall, these PT secreted factors are likely to promote metastatic progression in micrometastatic niches, 5 especially when autocrine release of growth supporting factors is insufficient.…”
Section: Discussionmentioning
confidence: 99%